Answers:
a. 3x+7=-x-1
Move -x to the other side. Sign changes from -x to +x.
3x+x+7= -x+x-1
3x+x+7= -1
4x+7= -1
4x+7-7= -1-7
4x= -8
divide by 4 for both sides
4x/4= -8/4
x= -2
b. 1-2x+5=4x-3
1+5-2x= 4x-3 - combine like terms
6-2x= 4x-3
move 6 to the other side
6-6-2x= 4x-3-6
-2x= 4x-9
Move 4x to the other side
Sign changes from 4x to -4x
-2x-4x= 4x-4x-9
-6x= -9
divide by -6
-6x/-6= -9/-6
9/6- reduce. divide by 3. 9/3= 3 , 6/3= 2
x= 3/2 and x= 1 1/2
c. 4x-2+x=-2+2x
4x+x-2= -2+2x
5x-2= -2+2x
5x-2x-2= -2+2x-2x
3x-2= -2
3x-2+2= -2+2
3x=0
divide by 3
3x/3= 0/3
x= 0
d. 3x-4+1=2x-5+5x
3x-3= 2x+5x-5
3x-3= 7x-5
3x-7x-3= 7x-7x-5
3x-7x-3= -5
-4x-3= -5
Move -3 to the other side
-4x-3+3= -5+3
-4x= -2
divide by -4
-4x/-4= -2/-4
x= 2/4 or reduce x= 1/2 ( divide by -2 : -2/-2= 1 , -4/-2= 2
Answer: x= 2/4 and x= 1/2